Mimesis and sacrifice: applying Girard's mimetic theory across the disciplines - Pally, Marcia (Violence, desire, and the sacred, 2019)
"Central to identity, personal responsibility, economic systems, theology, and the political and military imaginaries, the practice of sacrifice has inspired, disturbed, and abused. Mimesis and Sacrifice brings together scholars from the humanities, military, business, and social sciences to examine the role that sacrifice plays in different present-day settings, from economics to gender relations. Inspired by Rene Girard's work, chapters explore (i) the extent to which the social character of human living makes us mimetic, (ii) whether mimesis necessarily leads to competitive aggression, (iii) whether aggression must be defused by aggressive sacrificial rituals-and whether all sacrifice has this aim, and (iv) the role of the"second lesson of the cross" (as Girard called it), the lesson of self-giving for others, in addressing present societal problems. By investigating sacrifice across this span of arenas and questions yet within one volume, Mimesis and Sacrifice presents a new appreciation of its influence and consequences in the world today, contributing not only to mimetic theory but to greater understanding of which societal arrangement enable us to live well together and what hobbles that goal."--Bloomsbury Publishing